2017
DOI: 10.4103/jmh.jmh_34_17
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of oral lichen planus in perimenopausal women: A cross-sectional study in Western Uttar Pradesh population

Abstract: Background:Hormonal fluctuations during menopause lead to endocrine changes in women, especially in their sex steroid hormone production. Studies have documented the role of estrogen and progesterone (Pg) on autoimmune disorders such as multiple sclerosis, systemic lupus erythematosus, and rheumatoid arthritis. Lichen planus (LP), an autoimmune disorder, seen frequently in perimenopausal women, may also get affected by sex steroid hormones, but no direct relationship has been established yet.Aim:The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 20 publications
2
20
2
3
Order By: Relevance
“…16 A case control study conducted in a dental hospital found that in a sample of 365 postmenopausal women with routine dental complaints, 27.1% women had dry mouth, 25.8% had mucosal burning or pain sensation, 6.3% had breath change and 3.6% had change in taste. 11,17 15 of 82 women had oral lichen planus, which was higher than two previous studies having rates of 10.9% and 13.75% of patients respectively. 11…”
Section: Discussioncontrasting
confidence: 51%
“…16 A case control study conducted in a dental hospital found that in a sample of 365 postmenopausal women with routine dental complaints, 27.1% women had dry mouth, 25.8% had mucosal burning or pain sensation, 6.3% had breath change and 3.6% had change in taste. 11,17 15 of 82 women had oral lichen planus, which was higher than two previous studies having rates of 10.9% and 13.75% of patients respectively. 11…”
Section: Discussioncontrasting
confidence: 51%
“…OLP in peri and post-menopausal women can be mediated by the declined level of estrogen and Progesterone directly or indirectly through causing depression that can trigger LP. 19 Estrogen increases the activity of the enzyme responsible for activating Vit D, so declining estrogen levels during the menopausal transition could lead to symptoms of Vit D deficiency 20 . Hence, there is a strong correlation between vit D deficiency and the incidence of lichen planus.…”
Section: Discussionmentioning
confidence: 99%
“…Larsen, Johansen, Reibel, Zachariae, and Pedersen (2017) suggest that gender hormones may be involved in the pathogenesis by making the mucosa more susceptible to oral diseases such as OLP. Moreover, Mohan et al (2017) report that LP in perimenopausal women can be mediated by declined levels of oestrogen and progesterone causing depression that can trigger OLP.…”
Section: Discussionmentioning
confidence: 99%